Equality bodies in the European Union: The Spanish independent authority for equal treatment - Ángeles Solanes Corella (Deusto Journal of Human Rights, 2023)
The preceding two decades have been characterized by the evolution of equality bodies at the domestic level. Recently, several propositions have been advanced with the aim of instituting minimal prerequisites for the functioning of equality entities, aimed at enhancing their efficacy and ensuring their independence, thus fortifying the enforcement of the principle of equal treatment. In Spain, Law 15/2022 has provided for the creation of the Independent Authority for Equal Treatment and Non-Discrimination, but after the six months established for its configuration, it has not been set up. This work critically examines the proposed reforms within the Equality Directives concerning these bodies and their implementation in the case of Spain. At the same time, it assesses, from a proactive perspective, how to develop European standards in line with the proposal, so that equality bodies can deploy their full potential.